Different exercises for speed and agility and its effect on dribbling manovars and recovery for basketball players ages under 16 years - Mohammed, Nada (Journal of Physical Education, 2015)
This study aimed to develop speed and agility to find their effect on performance. the research proposed a set of exercises to accomplish his aim. the study hypothesized that there are a statistical effect of proposed exercises on skill executions. subjects were (13) players ages under 16 years. the represented the national center of basketball. subjects were tested in speed, accuracy, manover dribbling and recovery, after (18) sections of training. subjects were retest in the same tests under the same conditions. Results showed that the proposed exercises have statistical effect on those skills. the study recommended using these exercises to develop basic skills in basketball